Terms of specialized nursing language for people with pressure injury - Fernando Hiago da Silva Duarte; Wenysson Noleto dos Santos; Francisca Simone da Silva; Dhyanine Morais de Lima; Sâmara Fontes Fernandes; Richardson Augusto Rosendo da Silva
ABSTRACT Objective: to validate the terms of the specialized nursing language used in care for hospitalized patients with Pressure Injury, identified in nurses' records, mapping them with the terms of the International Classification for Nursing Practice (ICNP® 2017). Methods: methodological study, carried out at a School Hospital in 2018. It was performed: extraction of terms of medical records; normalization; cross-mapping between extracted terms and those in ICNP®; distribution in the seven axes; theoretical definition and validation of terms. Results: 27,756 terms were extracted. The normalization resulted in 370 relevant terms, being: 225 listed and 145 not listed in the ICNP®, being 60 similar, 13 more comprehensive, 38 more restricted and 34 without agreement, all of which are validated. Conclusion: this study identified and validated terms used by nurses to assist people with Pressure Injury. These may contribute to the unification of professional nursing language in care for these clients.